Determination of nutritional value of tachypleus gigas (horseshoe crab) - Nashrin Iszhan, Ishak; Nazikussabah, Zaharudin (2021)
Horseshoe crabs are marine arthropods of the family Limulidae, suborder Xiphosurida, and order Xiphosura[1]. Horseshoe crabs superficially resemble crustaceans but belong to a separate subphylum, Chelicerata, and are closely related to arachnids.